Role of ionic diffusion in polymer gel mediated growth (PMG) technique for the synthesis of nanoparticulate fillers - Sonawane, Pradip S.; Biradar, Santoshkumar S.; Radhakrishnan, S.; Kulkarni, B. D. (Materials Chemistry and Physics, 2007)
Polymer mediated growth (PMG), which forms an important method for synthesis of nanoparticles, has one of the ions bound by polymer matrix while the other is allowed to diffuse and react to form desired compound. The exact role of ionic diffusion in the formation of nanoparticles has been investigated by taking specific case studies. Typically calcium carbonate, calcium phosphate and calcium sulfate have been formed in nano-size by PMG route using polyacrylamide gel. The extent of cross-linking of the polymer matrix in the formation of gel, affects the diffusivity of ions into polymer matrix and the size of particles formed. The rates of diffusion for different extents of cross-linking of polymer are estimated during the synthesis of nanoparticles using Fick's law. The inter-correlation between the particle size formation and the diffusion length has been clearly brought out in these studies. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: ionic diffusion; nanoparticulate fillers; polymeric gels